Geopolitical risks for Egypt wheat supply and trade - Gebeltová, Zdeňka; Hálová, Pavlína; Malec, Karel; Bartoňová, Klára; Blažek, Vojtěch; Maitah, Mansoor; Koželský, Robert; Phiri, Joseph; Appiah-Kubi, Seth Nana Kwame; Tomšík, Karel; Severová, Lucie; Marušiak, Jiŕí (Frontiers in Sustainable Food Systems, 2023)
Since 2005, Russia has established a stable position in Egypt's wheat imports (with the exception of 2009, when the US dominance of world markets peaked, and 2013, when Ukraine started importing wheat into Egypt). Russia also became the largest exporter of wheat globally after 2016. The change in grain production on the Russian side has visibly translated into a change in wheat export destinations, in favour of developing countries. The main objective of the paper is to identify the main determinants of foreign wheat trade in Egypt in relation to the main risks associated with the war in Ukraine. A sub-objective is then to define the statistical relationship between the quantity of wheat imported into Egypt and the independent variables of the socio-economic domain. The paper is based on time series analysis, index analysis and econometric model. whose qualities are tested by the stationarity test (ADF test). The model was verified (ADF test), its dynamization and cointegration test (Johansen test) were performed. Egypt currently (2020) imports the same amount of wheat as it produces itself (9 million tons of wheat). Although the growth rate of wheat production in Egypt is increasing (1.9% p.a. over the period 2000-2020), with a growing population (2.01% p.a.), Egypt is not able to reduce the percentage of import dependence below 50% of total consumption. Despite the fact that wheat consumption has increased by 7% to 146 kg per capita over the period under review (2000-2020), the percentage of undernourished in Egypt still stands at 5.2-5.4% of the population. Moreover, the per capita vegetable protein intake (g/capita/day) is unfortunately declining (from 76.5 g in 2000 to 71.3 g in 2019). The econometric model shows: that the variables describing the evolution of production, population and prices are statistically significant in relation to wheat imports.